Urgensi Nilai Islam dalam Menghadapi Tantangan Teknologi Kontemporer - Muhammad Yalqa Rayyandhiya Azka; Jenuri Jenuri (Muttaqien, 2024)
In this era of rapid technological advancement, the technology sector is booming. Along with these advancements, complex moral and ethical challenges arise as a result of technological progress itself. This article will delve into the urgency of Islamic values in addressing these challenges and the impacts of technological development. Islamic values hold significant relevance in guiding Muslim individuals toward responsible technology use. This research employs a qualitative method with a literature review approach to examine the implications of Islamic values in addressing contemporary technological challenges, such as privacy protection and communication ethics. Through education, awareness, and the implementation of technology ethics grounded in Islamic values, individuals can mitigate the adverse effects of digital life, thus fostering a fairer, more inclusive, and sustainable society in this rapidly evolving digital age.